Multidrug-Resistant Uropathogens in Companion Animals: A Comprehensive Study from Clinical Cases and a Genomic Analysis of a CTX-M-14-Producing Escherichia coli ST354, a Leading Cause of Urinary Tract Infections - Sakauchi, Victoria T.S.; Silva, Bianca C.T.; Haisi, Amanda [UNESP]; Júnior, João P. Araújo [UNESP]; Ferreira Neto, José S.; Heinemann, Marcos B.; Gaeta, Natália C. (SAGE Publications, 2025)
Urinary tract infections (UTIs) are common in small animals, posing significant clinical challenges due to their recurrence and discomfort. This study investigated the bacterial causes and antimicrobial resistance patterns of UTIs in dogs and cats presented to an important Veterinary Teaching Hospital in São Paulo, Brazil, the largest city in Latin America. Samples were collected from 31 dogs and 9 cats via ultrasound-guided cystocentesis. Bacterial cultures were performed, species identification was accomplished with matrix-assisted laser desorption ionization-time of flight mass spectrometry, and antimicrobial susceptibility testing was done using the Kirby-Bauer method. Escherichia coli was the most frequently isolated pathogen, accounting for 27.9% of cases, followed by Staphylococcus pseudintermedius, Proteus mirabilis, and Klebsiella pneumoniae. Ampicillin resistance was observed in 70.4% of enterobacteria, with many E. coli strains exhibiting multidrug resistance. Whole-genome sequencing of an extended-spectrum beta-lactamase-producing uropathogenic Escherichia coli strain from a feline patient was performed; it was identified as ST354, a leading cause of UTIs worldwide in humans and animals, carrying the blaCTX-M-14 gene and other resistance determinants. Phylogenetic analysis indicated genetic proximity between this strain and others from Brazilian poultry and environmental sources. These findings emphasize the need for antimicrobial resistance surveillance in veterinary UTIs and advocate for stricter antibiotic stewardship to inform diagnostic and therapeutic approaches within a One Health perspective.
Keywords: cystitis; genomic analysis; One Health; small animals; surveillance